094 Introducing mindfulness to GOSH. (December 2018) - Bathgate, F
Abstract : Mindfulness is a form of awareness training that helps people relate more effectively to their experiences. It involves paying attention to thoughts, feelings and body sensations in a way that increases awareness, acceptance and self-compassion to help manage difficult experiences, and create space to make wise choices. Some families demonstrate resilience in the face of their child having a condition that is treated at GOSH. But others experience the demanding treatment regimes, the shift in roles, and responsibilities as stressful. Studies have found associations between parenting stress and adverse caregiver and child psychological sequelae (e.g. Mullins et al. 2004). Parenting stress may also affect child health-related outcomes as it can interfere with the management of a child's chronic condition (e.g. Barakat et al, 2007a). Mindfulness is associated with self-reported positive affect (Brown and Ryan, 2003), less anxiety and depression (Brown and Ryan 2003), greater relationship satisfaction and less relationship stress (Barnes et al. 2007). Mindfulness develops and enhances skills such as emotional intelligence, decision-making, communication, collaboration and teamwork, which are all skills important for the workplace. According to the Health and Safety Executive, UK businesses lose approximately £530 million a year due to stress-related illnesses. Given the elevated risks of burnout when working in healthcare, it would seem logical to bring Mindfulness to the healthcare workplace. As part of my Mindfulness Teacher training, I ran 8 week MBCT courses for staff and for parents. The intervention helped parents with clinical levels of stress and depression to reduce to below clinical thresholds. Although staff members were not scoring so highly on the same measure and so demonstrated less change, they did positively evaluate the course. Conclusion: Mindfulness is a useful intervention to offer in this setting; to parents to reduce levels of stress and depression, and to support staff well-being.